Laparoskopická resekce sigmatu pro divertikulární chorobu - Vrbenský, L; Simša, J (Rozhledy v chirurgii, 2013)
INTRODUCTION: Laparoscopic resection of the sigmoid colon for diverticular disease is nowadays a fully accepted alternative to traditional open procedures. AIM: The aim of this work is to summarize the indications, advantages and risks of laparoscopic sigmoid resection for diverticular disease. METHODS: Review of the literature and recent findings concerning the significance of laparoscopic resection for diverticulosis of the sigmoid colon. CONCLUSION: The article presents the indications, risks, techniques and perioperative care in patients after laparoscopic resection of the sigmoid colon for diverticular disease.
Keywords: Laparoscopy; Perioperative Care; Diverticulosis, Colonic; Humans; divertikulóza tlustého střeva; divertikl tlustého střeva; laparoskopie; lidé; Colon, Sigmoid; colon sigmoideum; perioperační péče; Diverticulum, Colon